2013
DOI: 10.1002/jmri.24274
|View full text |Cite
|
Sign up to set email alerts
|

Fractal analysis of spontaneous fluctuations of the BOLD signal in the human brain networks

Abstract: Our results support that the origin of RS-fMRI signals contains arterial fluctuations. Hence, in addition to the commonly used method such as synchrony analysis and power spectral analysis, another approach, the fractal analysis, is suggested for acquiring the information of hemodynamic responses by means of RS-fMRI data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…In this regard, Hofman was one of the first researchers who has shown that the cerebral cortex manifests fractality 16 , and this property was confirmed by other studies, including the works by Free et al and Kiselev et al who demonstrated, using different approaches, that the cerebral cortex presents statistical self-similarity 5,13 . More recently, the fractal analysis has also been effectively applied to time series of brain signals, e.g., in functional MRI [18][19][20] .…”
Section: Toward a More Reliable Characterization Of Fractal Propertiementioning
confidence: 99%
“…In this regard, Hofman was one of the first researchers who has shown that the cerebral cortex manifests fractality 16 , and this property was confirmed by other studies, including the works by Free et al and Kiselev et al who demonstrated, using different approaches, that the cerebral cortex presents statistical self-similarity 5,13 . More recently, the fractal analysis has also been effectively applied to time series of brain signals, e.g., in functional MRI [18][19][20] .…”
Section: Toward a More Reliable Characterization Of Fractal Propertiementioning
confidence: 99%
“…Indeed, fMRI time series have been analyzed by means of fractal analysis, demonstrating the ability of such an analysis to quantify the dysregulation of dynamic interactions between different limbic system regions in healthy adults in states of increased anxiety (Olejarczyk 2007). Fractal properties and applications of fractal analysis to fMRI can be found in the literature (Bullmore and others 2004; Li and Huang 2013; Rubin and others 2013).…”
Section: Fractal Analysis In Neuroimagingmentioning
confidence: 99%